Chronic Migraine: Diagnosis, Characteristics, Lifestyle Modification, Trigger Reduction and Treatment - Roshan Kumar Jha; Ranjit Ambad; Dhruba Hari Chandi; Obaid Noman (Journal of Pharmacy and Bioallied Sciences, 2024)
The most prevalent brain condition that impairs function is migraine. A chronic migraine is a very incapacitating disorder that is defined by having a migraine that lasts for at least 10 days every month. Chronic migraine patients commonly visit primary care, are advised to seek treatment in secondary care, and account for a large portion of the patient population in specialized headache clinics. Using a triptan, opioid, compound analgesic, or ergot derivative. A significant, curable cause of neurological impairment is chronic migraine. Making a diagnosis is essential, as is ensuring that any coexisting medical or psychiatric disorders are addressed concurrently with efforts to lessen the biological propensity for headaches. Setting patients’ expectations for what is possible is also crucial. Migraine cannot be “fixed” in any way; it is a hereditary propensity that fluctuates throughout a person’s life.